Percutaneous nephrolithotomy in a patient with cervical and dorsolumbar ankylosing spondylitis (Indian Journal of Case Reports, 2020)
Ankylosing spondylitis is a form of arthritis that typically develops in the lower back and hips and gradually progresses up toward the neck over time. Ankylosing spondylitis results in spinal deformities in the long-term. These cervical deformities make intubation difficult for the anesthetists and similarly cause difficulty in positioning the patient for percutaneous nephrolithotomy (PCNL) to the urologist. We report the case of a 61-year-old male who presented to us with bilateral urolithiasis. Physical examination revealed him to be having cervical kyphosis and dorsolumbar scoliosis. The anesthetic team performed nasal intubation with the patient in half-sitting position using a video laryngoscope. PCNL was performed with the patient lying prone and the chest and abdomen supported by pillows from beneath. Post-operative recovery was uneventful.